XVI-XVII a. kalendoriai Vilniaus universiteto bibliotekoje - Balčienė, Irena (Knygotyra, 1997)
Almanac - a book containing the days, weeks, and months of the year, along with information about festivals, astronomical data, and other items of interest. The article describes the oldest almanacs held in the Vilnius University Library. There are 5 almanacs from the 16th century, 6 from the 17th century, and many from the 18th century. Special focus is given to their provenances. The majority of almanacs came to the Vilnius University Library from monasteries (Vilnius, Dotnuva, Molodechno, etc.). Another part came from the personal libraries of famous individuals. Many of these books have several bookplates, indicating a complex history within Lithuanian culture.